2012
DOI: 10.1371/journal.pone.0044360
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Animal Model of Partial Optic Nerve Transection Established Using an Optic Nerve Quantitative Amputator

Abstract: BackgroundResearch into retinal ganglion cell (RGC) degeneration and neuroprotection after optic nerve injury has received considerable attention and the establishment of simple and effective animal models is of critical importance for future progress.Methodology/Principal FindingsIn the present study, the optic nerves of Wistar rats were semi-transected selectively with a novel optic nerve quantitative amputator. The variation in RGC density was observed with retro-labeled fluorogold at different time points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Previously, we have only used DARC to assess complete axotomy 29 —but interestingly, in that model, we also showed peak apoptosis to occur at 7 days, suggesting a similar temporal profile and course of RGC death. Similar results were found by Wang et al 40 recently, using histological analysis in the same pONT model, with peak RGC apoptosis at 1 week which gradually decreased over 12 weeks. One study showed different results, however, which may be attributed to different experimental protocols.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Previously, we have only used DARC to assess complete axotomy 29 —but interestingly, in that model, we also showed peak apoptosis to occur at 7 days, suggesting a similar temporal profile and course of RGC death. Similar results were found by Wang et al 40 recently, using histological analysis in the same pONT model, with peak RGC apoptosis at 1 week which gradually decreased over 12 weeks. One study showed different results, however, which may be attributed to different experimental protocols.…”
Section: Discussionsupporting
confidence: 91%
“…One study showed different results, however, which may be attributed to different experimental protocols. First, Levkovitch-Verbin et al 13 applied a milder insult cutting the ON to a depth of 0.1 mm compared with 0.2 mm in this study and approximately 0.4 mm in the study by Wang et al 40 —we and the others have previously shown that the extent of neurotoxicity is dependent on the magnitude of the insult. 41 , 42 Second, rat species and weights were different.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Another region of the central nervous system demonstrating variable responses to injury is the optic nerve. The optic nerve consists of axons from retinal ganglion cells, which integrate and relay visual information from the retina of the eye to visual centres in the brain (Fischer and Leibinger, 2012;Wang et al, 2012). In mammals and birds, damage to these axons can result in vision loss, as retinal ganglion cells degenerate and undergo cell death (Lang et al, 1998(Lang et al, , 2017Williams, 2017).…”
Section: Restoring the Optic Nervementioning
confidence: 99%